Pengaruh Prinsip Syariah, Kualitas Layanan, Produk, Dan Promosi Terhadap Keputusan Masyarakat Dalam Menggunakan Produk-Produk Bank Syariah Mandiri Di Kantor Cabang Pembantu Rogojampi Kecamatan Rogojampi Kabupaten Banyuwangi - Nur Moh. Annurroin (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2020)
Banking institutions are one of the most important institutions in the modern economic system. There is no modern country that runs its economic activities without involving banking institutions. Banking is an intermediary institution that functions as a liaison (intermediator) between surplus units and deficit units, by collecting funds from the public in the form of savings or deposits and then channeled back to the public in the form of credit or financing. in this study there are problems examined including sharia (religious) factors, service quality, product types and promotions that have positive and significant influence on community decisions and the most dominant factor influencing the community in using Bank Syariah Mandiri products in Rogojampi District, Banyuwangi Regency. This study aims to determine the factors that influence the community in using Bank Syariah Mandiri products in Rogojampi District, Banyuwangi Regency. Respondents were drawn from the public who are customers at Bank Syariah Mandiri located in Banyuwangi district with 6 offices using the accidental sampling technique. The method used to determine the relationship between the dependent variable and the independent variable is multiple linear regression, namely:Y = ao + b1 X1 + b2 X2 + b3 X3 + b4 X4 + e The results of multiple regression analysis show that the independent variables in this study have a positive and significant influence together on the dependent variable, namely the community's decision to use Bank Syariah Mandiri products, which shows that the most dominant factor influencing the community in using Bank Syariah Mandiri products , is the product factor. The partial test results show that the independent and dependent variables that have a positive and significant influence are product factors.